﻿Neuroprotective effects of a 40% ethanol extract of the black walnut bark (Juglans nigra L.) - Dmitry I. Pozdnyakov; Zhanna V. Dayronas; Denis S. Zolotych; Anastasya D. Geraschenko; Natalya B. Shabanova (Belgorod National Research University, 2022)
Introduction: Neuroprotection is a promising area of adjuvant therapy of ischemic brain lesions. At the same time, among potentially effective neuroprotectors, herbal remedies are distinguished due to their high efficiency and safety of use. In this work, some aspects of the neuroprotective effect of 40% ﻿ethanol﻿ extract of black walnut bark were investigated in comparison with its major component ﻿juglone﻿. Materials and methods: The work was performed on male Wistar rats, which were simulated with cerebral ischemia by irreversible occlusion of the middle cerebral artery. The acute toxicity of the extract was preliminarily evaluated. During the work, the following parameters were determined: changes in the behavior of animals in the Morris water maze, cerebral blood flow, brain necrosis zone area, the activity of mitochondrial complexes, citrate synthase activity, lactic, pyruvic, and ATP concentrations. The activity of the studied extract was compared with ﻿juglone﻿ in a concentration of 1 mg/kg (per os). Discussion: The study showed that the use of black walnut bark extract in conditions of cerebral ischemia contributed to an increase in the activity of mitochondrial complexes I-V, citrate synthase, which in turn led to the normalization of aerobic-anaerobic metabolism reactions. The increase in the activity of respiratory complexes is probably mediated by the antioxidant properties of ﻿juglone﻿, which is a major component of the test extract of black walnut bark. Conclusion: Thus, the test extract can be a potentially effective neuroprotective agent and requires further study.